Biblioteca antirracista: implementação de práticas antirracistas na Biblioteca Central da Universidade Federal de Sergipe (BICEN/UFS) - Souza, Mirele da Costa (2024)
Racism is a deeply rooted historical structure in Brazilian society, impacting on various spheres, including educational and cultural spaces, such as libraries. These institutions, which should be synonymous with access and inclusion, often reproduce inequalities, whether due to the lack of diverse collections or the absence of practices that directly address racism. In this scenario, racial literacy emerges as a fundamental tool to enable librarians to consciously recognize, understand and combat racism, transforming libraries into active agents in promoting racial equality. This research aims to investigate and encourage the implementation of anti-racist library practices at the Central Library of the Federal University of Sergipe (BICEN/UFS). Based on decolonial and black theories, the study reflects on the role of libraries as spaces for social transformation and the promotion of racial equality. The specific objectives include: mapping the cultural practices carried out by the institution's librarians in the context of ethnic-racial relations; analyzing the representativeness of the collections related to these themes; identifying the challenges in developing inclusive and anti-racist actions; investigating the role of librarians in promoting racial literacy, and proposing strategies to foster discussions and activities aimed at social equality. Adopting an exploratory methodology with a qualitative approach and supported by a literature review, the research seeks to understand the structural and institutional barriers that hinder the implementation of anti-racism policies in university libraries. The final product of the professional master's degree is the creation of a practical booklet designed to guide librarians in the application of racial literacy strategies. This guide will contribute to the implementation of anti-racist actions at BICEN/UFS, offering guidelines for effective inclusion in the library's services and activities, creating a more welcoming environment committed to social justice. In this way, the dissertation reinforces that the role of libraries goes beyond simply storing knowledge: they can and should be protagonists in the fight against racism and in building a fairer and more equal society.